Literary Portraits in the Novels of F. M. Dostoevskij - Heier, Edmund (Vortraege und Abhandlungen zur Slavistik, 1989)
In approaching F. M . Dostoevskij's novels with the express purpose of identifying and determining the function of literary portraiture, one is faced with an unexpected enormous gallery of literary portraits. These are verbal accounts or drawings in words, in which physical appearance and facial expression are described not only to evoke a visual image, but more specifically to discern the inner man. The vast amount of material that came to light in the pursuit of this study has necessitated a selection and omission of equally valid specimens, which would further substantiate that Dostoevskij was a close observer of the physical properties of his characters and that he employed them to delineate psychological and moral disposition.